Additions to the retrospective bibliography of Lithuanian books and their sources - Kaunas, Domas (Knygotyra, 2006)
The bibliographers of the Lithuanian National Martynas Mažvydas Library have written an open letter to the public asking to provide data about additions to the retrospective bibliography of old Lithuanian publications published in Vilnius in 1969. This act was inspired by the Consortium of European Research Libraries that started a project of database of the Hand Press Books published in 1455-1830. Lithuanian National Library is conducting retroconversion of the retrospective bibliography and provide data to the international database. This task will also lead to the creation of an original database of books and an electronic publication of it on CD-ROM. The specialists expect that bibliophiles and collectors will help to identify the additional publications. The request to investigate personal libraries looking for the books published before 1864 was made. The data on them should be sent to the creators of the bibliography. This article is a response to the call of bibliographers. It provides information about rare books collected in the personal library of the author. They allow to make changes of the scope of the bibliography and correct some bibliographic records. The data is organised according to the importance and subject: a) additions to the retrospective bibliography of books, b) copies of the books registered and described in the bibliography using sources, c) additional data to some bibliographic descriptions, d) unknown copies of rare books, e) valuable copies of books. This article also pursues a methodological purpose. It presents the personally acquired experience of data retrieval, acquisition and classification for supplementing of the retrospective bibliography as well as the methods of making and arguing the assumptions inevitable in the history of a book. The author believes that the registration of old books from personal libraries in bibliographies is an important task of accounting of the cultural heritage. It is very important for the countries of the size and fate of Lithuania. The manuscript and printed heritage registered in bibliographies enable us to evaluate its size, importance, location, dynamics of dissemination in social environment, and changing geography of owners. This can influence research and help to diminish the loss of cultural heritage during potential catastrophes or misfortunes with tragic consequences.
Keywords: -